‘ZS-MDR-TB’ versus ‘ZR-MDR-TB’: improving treatment of MDR-TB by identifying pyrazinamide susceptibility - Ying Zhang; Kwok Chiu Chang; Chi-Chiu Leung; Wing Wai Yew; Brigitte Gicquel; Dorothy Fallows; Gilla Kaplan; Richard E Chaisson; Wenhong Zhang (Emerging Microbes and Infections, 2012)
Indispensable for shortening treatment of drug-susceptible tuberculosis (TB), pyrazinamide (PZA, Z) is also essential in the treatment of multidrug-resistant (MDR)-TB. While resistance to PZA in MDR-TB is associated with poor treatment outcome, bacillary susceptibility to PZA along with the use of fluoroquinolone (FQ) and second-line injectable drugs (SLIDs) may predict improved treatment success in MDR-TB. Despite a high prevalence of PZA resistance among MDR-TB patients (10%–85%), PZA susceptibility testing is seldom performed because of technical challenges. To improve treatment of MDR-TB, we propose to: (i) classify MDR-TB into PZA-susceptible MDR-TB (ZS-MDR-TB) and PZA-resistant MDR-TB (ZR-MDR-TB); (ii) use molecular tests such as DNA sequencing (pncA, gyrA, rrs, etc.) to rapidly identify ZS-MDR-TB versus ZR-MDR-TB and susceptibility profile for FQ and SLID; (iii) refrain from using PZA in ZR-MDR-TB; and (iv) explore the feasibility of shortening the treatment duration of ZS-MDR-TB with a regimen comprising PZA plus at least two bactericidal agents especially new agents like TMC207 or PA-824 or delamanid which the bacilli are susceptible to, with one or two other agents. These measures may potentially shorten therapy, save costs, and reduce side effects of MDR-TB treatment.